A foreign policy for the Left - Walzer, Michael (New Haven : Yale University Press, 2018)
Something that has been needed for decades: a leftist foreign policy with a clear moral basis Foreign policy, for leftists, used to be relatively simple. They were for the breakdown of capitalism and its replacement with a centrally planned economy. They were for the workers against the moneyed interests and for colonized peoples against imperial (Western) powers. But these easy substitutes for thought are becoming increasingly difficult. Neo-liberal capitalism is triumphant, and the workers' movement is in radical decline. National liberation movements have produced new oppressions. A reflexive anti-imperialist politics can turn leftists into apologists for morally abhorrent groups. In Michael Walzer's view, the left can no longer (in fact, could never) take automatic positions but must proceed from clearly articulated moral principles. In this book, adapted from essays published in Dissent, Walzer asks how leftists should think about the international scene--about humanitarian intervention and world government, about global inequality and religious extremism--in light of a coherent set of underlying political values.
Machine generated contents note: One. Moments in Time Getting Things Right and Wrong -- Two. What Is Left Internationalism? -- Three. In Defense of Humanitarian Intervention -- Four. Is There an American Empire? -- Five. Global and Domestic Justice -- Six. World Government and the Politics of Pretending -- Seven. Left and Religion The Case of Islam -- Eight. Complex Formation of Our Battles.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed January 5, 2018).
JSTOR
Keywords: International relations -- Philosophy; International relations -- Political aspects -- United States; Relations internationales -- Aspect politique -- États-Unis.; POLITICAL SCIENCE -- Government -- International; POLITICAL SCIENCE -- International Relations -- General; International relations -- Philosophy; International relations -- Political aspects; United States